Menelaah Penyimpangan “Pengampunan Dosa” Dalam Perspektif Suhento Liauw - Hia, Sozanolo; Harefa, Julitinus; Hia, Meniati; Tangu, Rosanti Yowa; Sari Larosa, Ayu Sekar (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2024)
Forgiveness of sins is an essential and fundamental principle in Christian teachings, reflecting the love and compassion of God, which provides humans the opportunity to correct their mistakes and return to Him. However, according to Suhento Liauw's perspective based on local church theology, there are significant differences in understanding and interpretation. This study aims to conduct an in-depth analysis of the concept of forgiveness of sins according to Suhento Liauw within the framework of local church theology, with the objective of understanding and evaluating Suhento Liauw's comprehension as well as its implications and relevance to Christian teaching and spiritual practice. The research method used is a descriptive qualitative approach with literature study, where the data will be analyzed using content analysis and theological analysis methods. The findings indicate that Suhento Liauw's view on the concept of forgiveness of sins in local church theology considers believers as the subjects of forgiveness, so their sins are forgiven and erased before Jesus Christ. Meanwhile, Suhento Liauw rejects the notion that God the Father is also an object for believers seeking forgiveness. This research provides valuable contributions to theological discussions and thoughts regarding the forgiveness of sins, with the hope of producing a more accurate and beneficial understanding for the church and the broader Christian community, as well as enriching the understanding of forgiveness of sins in the context of local church theology.